The Effect of Voluntary Disclosure and Earnings Quality on Cost of Equity - A. Ardiansyah; Sylvia Veronica Siregar (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2013)
The objective of this research is to examine the level and effect of voluntary disclosure andthe earnings quality on cost of equity capital of listed manufacturing company inIndonesian Stock Exchange in 2008. This study uses secondary data from the annualreports of 75 manufacturing firms listed in Indonesia Stock Exchange (IDX) in 2008. Weuse multiple regressions to test hypotheses. We find that the average of voluntarydisclosure is only 29.7%, which indicates that firms’ disclosure in the annual report is stilllow. The result also shows that the level of voluntary disclosure, in contrary to expectation,has positive and significant effect on cost of equity capital. We find some evidences thatearnings quality can reduce cost of equity capital.Tujuan penelitian ini adalah untuk menganalisis pengaruh tingkat pengungkapan sukareladan kualitas laba terhadap cost of equity capital pada perusahaan manufaktur yang terdaftardi Bursa Efek Indonesia tahun 2008. Penelitian ini dilakukan pada 75 perusahaan yangmenjadi sampel penelitian. Hipotesis penelitian diuji menggunakan regresi linier berganda.Hasil penilaian atas indeks pengungkapan sukarela menunjukkan rata-rata indekspengungkapan sukarela hanya 29.7% sehingga dapat disimpulkan bahwa tingkatpengungkapan sukarela dalam laporan tahunan perusahaan masih rendah. Hasil penelitianmenunjukkan bahwa tingkat pengungkapan sukarela, berbeda dengan dugaan, mempunyaipengaruh positif signifikan terhadap biaya modal ekuitas. Ditemukan juga bukti bahwakualitas laba dapat menurunkan biaya modal ekuitas.